2020
DOI: 10.1039/c9cp03841h
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of reaction rates: application to archetypal SN2 nucleophilic substitutions

Abstract: This work outlines the development and application of a multiscale computational protocol to evaluate reaction rates of elementary reactions in internal natural coordinates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 69 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…This work mainly focuses on the possibility of nucleophile formation in the vicinity of the nDsbD Ox active site, as there have been numerous studies of nucleophile-mediated scission of the S-S bonds using both experimental and computational methods. 18,21,52,[66][67][68][69][70][71][72][73][74] Of note, Dopieralski et al, explored disulfide reduction by OH À using different model systems and reported that S N 2 at S (substitution on one of the sulfur) and a-elimination (proton abstraction from the a-carbon) as energetically comparable and feasible. 18,21 Similar to the cases mentioned above, Tyr 42 O À could also assist in the disulfide bond cleavage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This work mainly focuses on the possibility of nucleophile formation in the vicinity of the nDsbD Ox active site, as there have been numerous studies of nucleophile-mediated scission of the S-S bonds using both experimental and computational methods. 18,21,52,[66][67][68][69][70][71][72][73][74] Of note, Dopieralski et al, explored disulfide reduction by OH À using different model systems and reported that S N 2 at S (substitution on one of the sulfur) and a-elimination (proton abstraction from the a-carbon) as energetically comparable and feasible. 18,21 Similar to the cases mentioned above, Tyr 42 O À could also assist in the disulfide bond cleavage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the approach presented previously, 1 the relevant dynamics for the (slow) reactive event is described with just one reaction coordinate, s , which is defined as a function s = s ( R ), where R is the set of all of the coordinates of the system. In practice, s is built only from a subset of the coordinates of the atoms participating to the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Interpreting s as a “slow” coordinate and considering the rest of the coordinates as a thermal bath, one obtains the Fokker–Planck equation for the probability density P ( s , ṡ , t | s 0 , ṡ 0 ,0) of finding the system with reaction coordinate s and velocity ṡ at time t , if it was in ( s 0 , ṡ 0 ) at time 0. It is convenient to apply the change of coordinates x = s with μ the inertia associated to s , 1 k B the Boltzmann constant, and T the absolute temperature. The Fokker–Planck equation in the set ( x , v ) readswhereIn the latter equation, the streaming frequency and the collision frequency ω c = ξ / μ have been introduced together with the Maxwell–Boltzmann equilibrium probability densitywith and u ( x ) = U ( s )/ k B T .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations